Effects of Intravenous and Catheter Directed Thrombolytic Therapy with Recombinant Tissue Plasminogen Activator (Alteplase) in Non-Traumatic Acute Limb Ischemia; A Randomized Double-Blind Clinical Trial - Saroukhani, Abbas (Bull Emerg Trauma, 2015)
OBJECTIVE: To evaluate the efficacy and safety of intravenous and catheter directed thrombolysis by recombinant tissue plasminogen activator (Alteplase) in the patients with non-traumatic acute limb ischemia (ALI). METHODS: This was a randomized clinical trial being performed between 2009 and 2011 in Mashhad University of Medical Sciences. We included those patients who were<75 years, with symptoms of less than 14 days duration, ALI of grade IIa and IIb (according to Rutherford classification) and absence of distal run off. Baseline assessment of peripheral circulation performed in all the patients. Patients were randomly assigned to undergo intravenous (n=18) or catheter directed thrombolysis (n=20) with Alteplase. The primary endpoint of the study was improvement of clinical status measured by Rutherford classification, ankle brachial index (ABI), visual analogue scale (VAS) score measured at 1, 3 and 6 months. The secondary endpoint of the study was complete or near complete recanalization of the occluded artery. RESULTS: A total number of 38 patients with mean age of 54.13±13.5 years were included in the study. There were 23 (60.5%) men and 15 (39.5%) women among the patients. Overall 3 (7.9%) patients had upper and 35 (92.1%) lower extremity ischemia. There was no significant difference between two study groups. None of the patients experienced major therapeutic side effects. Both ABI and VAS score improved in patients who have received first dose of t-PA within 24-hourof ALI. There was no significant difference between two study groups regarding the 6-month clinical grade (p=0.088), VAS score (p=0.316) and ABI (p=0.360). The angiographic improvement was significantly higher in CDT group (p<0.001). CONCLUSION: Intravenous and catheter directed thrombolysis with t-PA is a safe and effective method in treatment of acute arteriolar ischemia of extremities. However there both intravenous thrombolysis and CDT are comparable regarding the clinical outcome.